Primary peritoneal hydatid cyst in a child discovered during appendicular peritonitis - Hind Cherrabi; Halima El Mahfoudi (Elsevier, 2021)
Morocco is considered an endemic country for hydatidosis.Peritoneal localization is frequent in its secondary form, however, primary peritoneal hydatidosis is exceptional, especially in children.We report the observation of a 14-year-old child admitted for generalized abdominal pain with fever; the radiological assessment objectified two pelvic collections.Surgical exploration revealed a huge peritoneal hydatid cyst incidentally discovered associated with peritonitis of appendicular origin.The cyst was completely removed combined with appendectomy and peritoneal lavage.The post-operative evolution was simple.